2023
DOI: 10.3390/ijerph20146389
|View full text |Cite
|
Sign up to set email alerts
|

Community Perceptions of HIV Stigma, Discriminatory Attitudes, and Disclosure Concerns: A Health Facility-Based Study in Selected Health Districts of South Africa

Abstract: Research data about HIV stigma perceptions and discriminatory attitudes among the general population are limited. Furthermore, the willingness of HIV-negative individuals to engage with HIV prevention and disclosure interventions has not been established in South Africa. The study investigated community perceptions of stigma as well as discriminatory attitudes towards HIV disclosure to understand if and how these perceptions might influence the uptake of disclosure interventions. This facility-based study used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
2
5
0
Order By: Relevance
“…Furthermore, the fear of stigma affected clinic attendance as some of them skipped their clinic appointment to avoid being seen collecting their medication. Other studies reported similar findings [14,15,30]. Similar to previous studies, APHIV felt burdened by keeping their HIV status secret, which deprived them of emotional and psychosocial support from significant others [3,10,33].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, the fear of stigma affected clinic attendance as some of them skipped their clinic appointment to avoid being seen collecting their medication. Other studies reported similar findings [14,15,30]. Similar to previous studies, APHIV felt burdened by keeping their HIV status secret, which deprived them of emotional and psychosocial support from significant others [3,10,33].…”
Section: Discussionsupporting
confidence: 71%
“…Fear of stigma was a major challenge that contributed to APHIV keeping their HIV status a secret. Previous studies reported on how stigma and prejudice against HIV influenced APHIV to keep their HIV status a secret [13,[30][31][32]. Secrecy affected their adherence to ART as they missed taking their medication in the presence of friends and other people [4].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from this present study suggests that anticipated and experienced stigma within communities are barriers to healthcare access and treatment adherence for people living with HIV. Research shows that high and persistent levels of anticipated stigma may result in non-adherence to ART, disengagement in care, and non-disclosure amongst ALHIVs [ 51 , 52 , 53 , 54 ]. Additionally, a study conducted in Rwanda found that anticipated stigma was common amongst PLHIV, as it was sometimes experienced within communities and health facilities, often leading to early disengagement from care [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, putting Ubuntu ethics to use, one may prevent the stigmatization of HIV and TB and the hatred that fuels it. Additionally, treating PLHIV with dignity and respect will accept them as fellow human beings, especially in South Africa, where stigma and discriminatory attitudes are pervasive [41]. As a result, TB and PLHIV will be able to live dignified lives and experience the humanity that Ubuntu promises.…”
Section: Discussionmentioning
confidence: 99%